Publishing Mathematics On The Web A Survey Of Simple, Inexpensive Methods. - Purba, Harja Santana; Embong, Abdullah (2005)

(untitled)
There are a variety of approaches and technologies for publishing mathematics document on the Internet. In this paper we highlight three different methods, which have different purposes and applications. They are: direct embedding in HTML, page-oriented format, and advanced markup languages. The first method is suitable for integrating mathematical expression with other media such as movies, sounds, interactivity, data access, etc. The second method is used when we want post mathematical material in a form that is as close as possible to the original format, such as for printing or display locally. The last method is especially useful for integrating mathematical material with other Web technology, such as scripting languages. There are many tools available for authoring mathematical expression with little or no cost. The main tools are needed for encoding and validating HTML, CSS, XML, and MathML documents. Authoring mathematical document also needs an equation editor for creating mathematical expression. Other tools are needed for editing and converting mathematical document to eBooks format, such as PDF, LIT, HLP, and CHM generator.